Case Report Continuous Errector Spina Plane Blockspinaeas An Alternative To Epidural Analgesia During Thoracotomy Surgery - Andriyanto, Wahyu Prasetyo; Susila, Dedi (Journal of Neonatal Surgery, 2025)
Thoracotomy is a major surgical procedure that often causes severe postoperative pain, thus requiring optimal analgesic management. Erector Spinae Plane(ESP) Block has emerged as a promising alternative to epidural analgesia, with a lower risk of complications and good efficacy. This report presents a case of a 43-year-old male patient diagnosed with a mediastinal abscess with a possible lung tumor and chronic empyema on the chest tube for four months. The patient underwent right pulmonary decortication thoracotomy under Continuous ESP Block anesthesia. This procedure was performed under ultrasound guidance using a pediatric epidural catheter at the T4 level. Ropivacaine 0.5% was given as a loading dose of 20 ml, followed by maintenance ropivacaine 0.2% at a 7 ml/hour rate throughout the operation. This technique involves injecting a local anesthetic into the tissue layer near the erector spinae muscles to block sensory nerves that carry pain signals from the surgical area. The results showed effective analgesia with adequate pain control during and after surgery, without complications such as infection, hematoma, or nerve damage. The use of ESP Block also reduced dependence on systemic opioids and improved the patient's oxygen saturation. Thus, ESP Block provides a better safety profile with a shallower technique compared to epidural analgesia. In this case, Continuous ESP Block proved to be a valuable alternative for post-thoracotomy pain management, making it a reliable option for patients with contraindications or high risk to epidural techniques